Puzzling the parables of Jesus : methods and interpretation - Zimmermann, Ruben, 1968- (Fortress, 2015)
Modern scholarship on the parables has long been preoccupied with asking what Jesus himself said and what he intended to accomplish with his parables. Ruben Zimmermann moves beyond that agenda to explore the dynamics of parabolic speech in all their rich complexity. Introductory chapters address the history of research and distinguish historical from literary and reader-oriented approaches, then set out a postmodern hermeneutic that analyzes narrative elements and context, maps the sociohistorical background, explores stock metaphors and symbols, and opens up contemporary horizons of interpretation. Subsequent chapters then focus on one parable from early Christian sources (Q, Mark, Matthew, Luke, John, and the Gospel of Thomas) to explore how parables function in each literary context. Over all reigns the principle that the meaning or theological "message" of a parable cannot be extracted from the parabolic form; thus the parables continue to invite hearers' and readers' involvement to the present day